Knowledge on Pesticide Handling Practices and Factors Affecting Adoption of Personal Protective Equipment: A Case of Farmers from Nepal - Sandesh Thapa; Bipana Thapa; Rinicha Bhandari; Dinesh Jamkatel; Pooja Acharya; Sara Rawal; Sarika Bista; Ramesh Singh; Anuska Prasai; Srijana Bharati; Alesha Basnet (Advances in Agriculture)
Globally, the use of pesticide is growing day by day, but the use of PPE in developing countries is still low and farmers are directly exposed to chemicals which have negative health issues. Thus, this study was conducted in different places of Nepal where the use and adoption of chemical pesticide is high. This study aims on assessment of pesticide handling practices and determinants of adoption of PPE where 281 respondents were interviewed by the simple random sampling technique. A binary logit model was used to predict the determinants for adoption of PPE while spraying pesticides. Schooling years, training, reading label, and buying pesticide by name are the determining factors in adoption of PPE at 1% level of significance in the logit model. Still, the pesticide handling practices followed by farmers are not satisfactory and proper protective clothes are not used while spraying pesticides. Thus, to protect from different health issues, training, seminars, and talk discussion should be scheduled regarding safe pesticide handling practices and adoption of PPE. Also, the use of biopesticides should be encouraged as they are most promising and ecofriendly.